2019
DOI: 10.1101/658542
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The neonatal microenvironment programs conventional and intestinal Tbet+γδT17 cells through the transcription factor STAT5

Abstract: 15Interleukin(IL)-17-producing RORγt + γδ T (γδT17) cells develop in the embryonic thymus and 16 participate in type 3 immune responses. Herein we show that γδT17 cells rapidly proliferate within 17 neonatal lymph nodes and gut, where upon entry they uniquely upregulate Tbet and co-express IL-18 17, IL-22 and interferon(IFN) γ in a STAT3 and retinoic acid dependent manner. Neonatal 19 expansion was halted in mice conditionally deficient in STAT5 and its loss resulted in γδT17 cell 20 depletion from all adult o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 62 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…We have previously shown that antagonization of cIAP1 and cIAP2 in Th17 cells downregulates Il17a and Maf through the non-canonical NF-κB transcription factors RelB and p52 (Rizk et al, 2019). Thus, it is plausible that a similar mechanism exists in γδT17 cells; as such, the lack of cIAP1 and cIAP2 in γδT17 activates the non-canonical NF-κB, which downregulates Maf expression.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…We have previously shown that antagonization of cIAP1 and cIAP2 in Th17 cells downregulates Il17a and Maf through the non-canonical NF-κB transcription factors RelB and p52 (Rizk et al, 2019). Thus, it is plausible that a similar mechanism exists in γδT17 cells; as such, the lack of cIAP1 and cIAP2 in γδT17 activates the non-canonical NF-κB, which downregulates Maf expression.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously shown that the non-canonical NF-κB transcription factor RelB downregulates the expression of the transcription factor cMAF in Th17 cells; this occurs following the activation of the non-canonical NF-κB pathway through depletion of cIAP1 and 2 by SMAC mimetic compounds (Rizk et al, 2019). Thus, we hypothesized that the lack of cIAP1 and 2 expression in γδT17 activates the non-canonical NF-κB pathway and mobilizes RelB to downregulate cMAF.…”
Section: Activation Of the Non-canonical Nf-κb In γδT17 Cells Downregmentioning
confidence: 95%
See 3 more Smart Citations